Business-Led Corporate Responsibility Coalitions: Learning from the example of Business in the Community. - Grayson, David (Cranfield University School of Management, 2007)
Business in the Community (BITC) in the UK is the largest and one of the oldest business-led coalitions dedicated to corporate responsibility. This paper, written by one of the organisation’s former Managing-Directors and a longstanding staff member for more than twenty years, documents the evolution of BITC from a group dedicated to regenerating local economies through charitable contributions, to one concerned with integrating sustainability into its members’ core business strategies. BITC has helped to institutionalise and mainstream the practice of corporate responsibility. The author documents the organisation’s accomplishments as well as missed opportunities. The story offers lessons for the potential of business-led coalitions in galvanizing change and building the civil economy.
In partmnership with the Fellows of Harvard College